Comparative Study of Sol-Gel and Green Synthesis Technique Using Orange Peel Extract to Prepare TiO2 Nanoparticles - Hind Fadhil Oleiwi; Aseel J. Rahma; Siham I. Salih; Ammar A. Beddai (مجلة بغداد للعلوم, 2024)
Plant extracts have been widely explored as a safer alternative to conventional procedures for the manufacture of metal oxide nanoparticles. The present research concentrated on the synthesis and characterization of Titanium dioxide nanoparticles (TiO2NPs) using an environmentally friendly green synthesis approach (orange peel extract) compared with another technique (Sol-Gel method) at room temperature. The TiO2 nanoparticles were analyzed using an X-ray Diffraction (XRD) to determine the polycrystalline with Tetragonal structure anatase phase and  average crystallite size 30.2 nm and 24.2nm of the sample prepared from Sol-gel and green methods respectively. FTIR spectroscopy was used to determine the functional groups of TiO2 nanoparticles and their bonding nature. UV-Vis for optical properties shows the band gap energy of 2.85 eV and 3 eV for TiO2 nanoparticles were prepared using sol-gel and green methods respectively. FESEM analysis identified the morphology of the surface of TiO2 nanoparticles with the diameters of nanoparticles in the range of 60-80 nm  and 75-85 nm  were prepared via sol-gel and green methods respectively.